Calcitriol–PKM2 axis drives transcriptional and metabolic reprogramming of ILCPs into intestinal dual-cytokine-producing ILC3s - Qingyang Liu; Yidan Wang; Yanxiu Li; Yiyan Wang; Wei Liu; Steven Rosen; Fang Liang; Tingting Xie; Yang Xia (Proceedings of the National Academy of Sciences, 2026)
Vitamin D deficiency is associated with dysregulated alloimmune responses, but the mechanisms by which its active metabolite calcitriol shapes innate lymphoid cell (ILC) development and function remain incompletely understood. Here, we elucidate how calcitriol directs the differentiation of bone marrow (BM) ILC progenitors (ILCPs) into anti-inflammatory ILC3s with therapeutic potential in alloimmune diseases. Using murine vitamin D models, integrated omics, 13 C-glucose tracing, humanized mouse models, and clinical samples, we show that calcitriol, through the vitamin D receptor (VDR), selectively promotes the expansion and differentiation of BM ILCPs into IL-10 + IL-22 + ILC3s that exert tissue-protective effects in the intestine. Calcitriol-primed BM ILCP cell therapy attenuates intestinal inflammation in an alloimmune setting. Mechanistically, a VDR–SYK axis triggers nuclear translocation of pyruvate kinase M2 (PKM2). Nuclear PKM2 phosphorylates STAT3 at Tyr705, forming a dimerization complex with c-JUN that drives Il10 transcription. Simultaneously, cytosolic PKM2 channels pyruvate into pyruvate carboxylase–mediated mitochondrial anaplerosis, sustaining oxidative phosphorylation while suppressing reverse electron transport-driven mitochondrial ROS production. In human studies, patients with severe alloimmune complications exhibit reduced circulating ILCPs and low serum 25(OH)D levels. Calcitriol-treated human CD117 + ILCPs efficiently generate IL-10-producing ILCs in vitro and in humanized models, potently suppressing alloreactive T cell responses. Collectively, calcitriol reprograms BM ILCPs via the VDR–SYK–PKM2 axis to generate dual-cytokine IL-10 + IL-22 + ILC3s, establishing PKM2 as a key immunometabolic target and supporting calcitriol-primed ILCP-based cell therapy as a promising approach for alloimmune diseases.